Galectin-9 contributes to the pathogenesis of atopic dermatitis via T cell immunoglobulin mucin-3 - Su, Wenxing; Zhang, Ji; Yang, Shun; Tang, Minhui; Shen, Yu; Liu, Cuiping; Ji, Jiang; Maurer, Marcus; Jiao, Qingqing (Frontiers in Immunology, 2022)
Background: Atopic dermatitis (AD), a common type 2 inflammatory disease, is driven by T helper (TH) 2/TH22 polarization and cytokines. Galectin-9 (Gal-9), via its receptor T cell immunoglobulin- and mucin-domain-containing molecule-3 (TIM-3), can promote TH2/TH22 immunity. The relevance of this in AD is largely unclear. Objectives: To characterize the role of TIM-3 and Gal-9 in the pathogenesis of AD and underlying mechanisms. Methods: We assessed the expression of Gal-9 and TIM-3 in 30 AD patients, to compare them with those of 30 healthy controls (HC) and to explore possible links with disease features including AD activity (SCORAD), IgE levels, and circulating eosinophils and B cells. We also determined the effects of Gal-9 on T cells from the AD patients. Results: Our AD patients had markedly higher levels of serum Gal-9 and circulating TIM-3-expressing TH1 and TH17 cells than HC. Gal-9 and Tim-3 were linked to high disease activity, IgE levels, and circulating eosinophils and/or B cells. The rates of circulating TIM-3-positive CD4+ cells were positively correlated with rates of TH2/TH22 cells and negatively correlated with rates of TH1/TH17 cells. Gal-9 inhibited the proliferation and induced the apoptosis of T cells in patients with AD, especially in those with severe AD. Conclusion: Our findings suggest that Gal-9, via Tim-3, contributes to the pathogenesis of AD by augmenting TH2/TH22 polarization through the downregulation of TH1/TH17 immunity. This makes Gal-9 and TIM-3 interesting to explore further, as possible drivers of disease and targets of novel AD treatment.